(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Maize ear rot disease (cob rot) may occur either as a pre-harvest (causing kernel rots) after harvest. Fusarium graminearum, have been reported to be the most common causative agents of maize ear rots. Grain losses due to these ear rots are usually in the form of reduced grain-fill and weight. Pre-harvest infection can cause significant rotting on as many as 50-75% of the ears in a field under epidemic conditions. Data obtained were analyzed statistically using SPSS. Observations were presented in tables and pictorial forms using bar charts designed in Microsoft office 2013 excel sheets. Information from the farmers indicated that the occurrence of the pathogen varied in the various areas surveyed. The frequency of the disease showed that Biu had the highest average infection of 19.78%, followed by Hawul and Askira/Uba with 15.56% each, Damboa (13.33 %), Bayo (11.11%) while Chibok, Shani and Kwaya had the least infection of 8.89. Farmers interviewed indicated they are aware of maize ear rot disease and how it compromised grain quality. It was established that maize ear rot is caused by several factors among which were the variety of maize grown and the quantity of rainfall received.. It is recommended that that farmers should obtained their seeds from certified seed dealers.